2015
DOI: 10.4254/wjh.v7.i28.2792
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C genotype 4: The past, present, and future

Abstract: Hepatitis C virus (HCV) genotype (GT) 4 represents 12%-15% (15-18 million) of total global HCV infection. It is prevalent in Northern and Equatorial Africa and the Middle East, and is also present in some countries in Europe. GT-4 (and subtype 4a in particular) dominates the HCV epidemic in Egypt. In underdeveloped countries, risk factors associated with HCV infection may be due to unsafe medical practices or other factors such as familial transmission, mother's HCV status, or illiteracy. HCV prevention and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 186 publications
2
33
0
Order By: Relevance
“…Notably, genotype 4a is the most common HCV variant in Egypt (78% of cases). HCV genotype 4 represents more than 17 million total global HCV infections and is prevalent in Africa, the Middle East, and some European countries [29,30]. The analysis of HCV genotype 4 in Egypt demonstrated that HCV genotype 4a is extremely variable from other genotypes in terms of sequences and immunological determinants that might alter virus-host interaction and cytokine production [31].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, genotype 4a is the most common HCV variant in Egypt (78% of cases). HCV genotype 4 represents more than 17 million total global HCV infections and is prevalent in Africa, the Middle East, and some European countries [29,30]. The analysis of HCV genotype 4 in Egypt demonstrated that HCV genotype 4a is extremely variable from other genotypes in terms of sequences and immunological determinants that might alter virus-host interaction and cytokine production [31].…”
Section: Discussionmentioning
confidence: 99%
“…In study GS‐US‐342‐1138, all GT4 patients treated with SOF/VEL for 12 weeks achieved SVR12 . Other recommended treatments for GT4 HCV infection include combinations of NS3 protease inhibitors, NS5A inhibitors, NS5B polymerase inhibitors and/or ribavirin, with SVR rates above 90% (ombitasvir/paritaprevir/ritonavir + ribavirin, elbasvir/grazoprevir) …”
Section: Introductionmentioning
confidence: 99%
“…These subtypes are of interest because subtype 4r is not commonly reported while 4d is mostly reported in Saudi Arabia and in the majority of European IDU population [9, 28, 30, 36]. This result is thus different from studies in other African countries where subtypes 4a is the predominant subtype in Egypt [28, 35], 4f in Cameroon [37], 4e in Gabon [10, 29], 4k in the Central African Republic and Democratic Republic of the Congo [20, 38], 4c in the Republic of Congo [39], and 4q/4v in Rwanda [20]. The high diversity and predominance of genotype 4 suggests that this genotype has been endemic for a longer time in Ethiopian population.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, genotype 4 is considered difficult to treat and has a poor sustained virological response rate of 43–63% to the standard pegylated IFN/ribavirin combination therapy [32]. This is relatively higher than genotype 1 but lower than genotypes, 2, 3, 5, and 6 [34, 35]. …”
Section: Discussionmentioning
confidence: 99%